'Shadowing' as a management strategy for chemotherapy outpatient primary support persons. Issue 4 (25th January 2017) - McKenzie, Heather; White, Kate; Hayes, Lillian; Fitzpatrick, Scott; Cox, Keith; River, Jo
Abstract : Despite growing numbers of patients with cancer receiving chemotherapy in outpatient settings and the corresponding increase in care demands on family and close friends, little is known about the experiences of those informal carers supporting people with cancer during their chemotherapy trajectories. Using an interpretivist theoretical framework, this study explored the experiences of primary support persons of chemotherapy outpatients through in‐depth interviews with 17 participants nominated as their primary support persons by people receiving chemotherapy at a large tertiary hospital in Australia. The study demonstrates that primary support persons of chemotherapy outpatients face distinct challenges, being at the frontline of treatment and managing side effects with minimal support at home. This role involves sensitive provision of complex medical and social care in circumstances that profoundly challenge the everyday worlds of both patient and carer. From the moment of diagnosis, informal carers in this context face the 'double whammy' of needing to 'manage' the cancer diagnosis experience as well as the chemotherapy trajectory experience. This study points to the significant level of responsibility that primary support persons take on, and the extent to which patients and clinicians rely on their support and management skills. It also points, however, to the lack of recognition they receive for assuming this role, and their sense of frustration in the face of this invisibility. The conceptualisation of the informal carer role as a 'shadowing' role explicitly represents the protective, vigilant, but almost invisible, support role described by the participants in this study.